Clinicopathological risk factors in the light of the revised 2018 International Federation of Gynecology and Obstetrics staging system for early cervical cancer with staging IB: A single center retrospective study. Issue 16 (April 2020) - Zeng, Jing; Qu, Pengpeng; Hu, Yuanjing; Sun, Peisong; Qi, Ji; Zhao, Guiling; Gao, Yan
Abstract : Abstract: To validate the revised 2018 International Federation of Gynecology and Obstetrics (FIGO) staging system for cervical cancer on the survival of patients who underwent radical hysterectomy for 2009 FIGO stage IB carcinomas. We retrospectively identified and reviewed 251 patients treated with radical hysterectomy for 2009 FIGO stage IB cervical carcinomas from January 2011 to December 2016. The re-staged IB cohort consisted of 2018 FIGO stage IB1 (tumor size <2 cm), IB2 (2–3.9 cm), IB3 (≥4 cm), and IIIC1p (any pelvic nodal metastasis) cervical cancer. The univariate log-rank test and multivariate Cox regression models were performed for all potential clinic pathological risk factors based on cancer stage. On re-staging the 251 patients with 2009 FIGO stage IB using the 2018 FIGO staging system, 96 patients (38.2%) had stage IB1, 109 patients (43.4%) had stage IB2, 28 patients (11.2%) had stage IB3, and 18 patients (7.2%) had stage IIIC1p. The 5-year overall survival (OS) rates of patients with 2018 FIGO stage IB1, IB2, IB3, and IIIC1p were 97.9%, 92.7%, 78.6%, and 61.1%, respectively. The 5-year progression-free survival rates were 97.9%, 92.7%, 63.7%, and 20.8%, respectively. Factors significantly affecting OS and disease-free survival were 2018 FIGO stage≥IB3, histologic grade 2–3, and lymph node involvement. The revised 2018 FIGO staging system seemed to accurately reflect the survival rate, with a distinct statistical tendency for poorer 5-year disease-free survival and OS rates with increasing stage. Women with positive lymph nodes in this classification were classified as having stage IIIC disease, which can achieve more realistic survival results than the previous staging system. The prognostic discrimination of histologic grade should be considered when revising the staging system in the future.